Effect of Aluminium Fluoride on the Structure and Properties of Cryolite Alumina Molten Salt System. (September 2020) - Tian, Guocai; Wang, Yongzhi
Abstract: The influence of aluminium fluoride AlF3 on the structure and properties of cryolite-Al2 O3 melts are studied by molecular dynamics simulations at 1283 K and 0.1 MPa. The structure property such as radial distribution functions and coordination numbers, and the physical-chemical property such as density, conductivities, diffusion coefficients, and viscosities of the systems are obtained. It is shown that with the increase of aluminium fluoride content, fluorine ions in (Na3 AlF6 +4%Al2 O3 )1- w (AlF3 ) w molten salt system will replace the position of oxygen in alumina to form aluminium oxy-fluoride ion group, while aluminium ion group will form larger aluminium composite ion group through the connection of oxygen bridge and fluorine bridge. The formation of these ionic groups results in the decrease of the diffusion coefficient of anion and anion, the increase of viscosity and the decrease of conductivity in (Na3 AlF6 +4%Al2 O3 )1- w (AlF3 ) w, molten salt system.